Modified mesoporous biochar adsorbent and preparation method and application thereof
Through the preparation system of ionic liquid cascade metal inorganic salt, white carbon black and chitosan activation treatment straw, the problem of limited chemical functional group load in porous carbon materials in the aqueous solution system is solved, and the adsorption capacity of CO2 and NO is significantly improved, achieving the realization of It can efficiently remove gaseous pollutants from industrial flue gas.
Patent Information
- Application Number
- CN202411061404.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-08-05
AI Technical Summary
In the existing CO2 capture technology, the adsorption capacity of solid adsorbents is low and the energy consumption is high. The chemical functional group load of porous carbon materials is limited in the aqueous solution system, making it difficult to effectively improve the adsorption efficiency of CO2 and NO.
The preparation system for the activation treatment of straws with ionic liquid cascade metal inorganic salts, white carbon black and chitosan is adopted. Through the integrated pretreatment method of carbon activation, the alkaline functional groups and mesoporous structure of the carbon material surface are increased, and the ionic liquid and carbon are promoted. The interaction of the skeleton achieves efficient loading of S, N, and O active groups, significantly increasing the chemoadsorption capacity of CO2 and NO.
The adsorption capacity of CO2 and NO is significantly improved, the stability and economic benefits of the adsorbent are enhanced, the preparation cost is reduced, and gaseous pollutants in industrial flue gas are efficiently removed.
Smart Images

Figure CN118698501B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorption materials, and specifically relates to an ionic liquid modified mesoporous biochar adsorbent and a preparation method and application thereof. Background Art
[0002] Heavy industry is a basic industry and an important part of the national economy. The tail gas of the steel, cement, chemical, and fat industries still contains a large amount of carbon dioxide (CO2) and nitric oxide (NO) gases. Carbon dioxide is the most important greenhouse gas. Large-scale emissions of carbon dioxide will cause the temperature in the atmosphere to continue to rise, thereby triggering global climate change, such as melting glaciers and expanding oceans, which will in turn cause sea level rise, and will also cause ecosystem disorder and loss of biodiversity. Nitric oxide easily forms corrosive acid mist with moisture in the atmosphere, which is highly corrosive to equipment and buildings, and will seriously pollute the environment, thereby seriously endangering plant and human health. Therefore, how to reduce CO2 and NO gas emissions is one of the main challenges in the field of air pollution control.
[0003] The safe concentration of CO2 in the atmosphere should be lower than 0.035%, so it is urgent to carry out research on CO2 gas capture and storage (CCS) technology. CCS technology includes three links: capture, transportation and storage. The capture link requires the highest cost, accounting for up to 70% of the total technical cost. At present, the CO2 capture technology used in industry can be divided into: pre-combustion capture, oxygen-enriched combustion and post-combustion capture. Among them, post-combustion capture technology is considered to be the most feasible CO2 capture technology at present because of its wide range of applications and low requirements for equipment modification.
[0004] The performance of capture materials is the core of post-combustion capture technology. Post-combustion CO2 capture materials are mainly divided into liquid absorbents, membrane materials and solid adsorbents. Commonly used liquid absorbents mainly include organic amines, ammonia water, etc., but this method has defects such as high energy consumption in the regeneration process, corrosive liquids, and easy oxidation degradation or volatilization. Membrane separation is used for CO2 capture. The process does not require the use of solvents, the operation process is simple, and the footprint is small, but it is difficult for membrane materials to simultaneously meet the high selectivity and high permeability of CO2, and large-scale application is limited. Compared with other technologies, the adsorption method has attracted the attention of a large number of researchers due to its advantages such as low energy consumption, small modification of existing equipment, high selectivity, and relatively stable removal efficiency. Solid adsorbents include biochar, zeolite, metal organic framework materials (MOFs) and calcium-based adsorbents. Among them, porous carbon materials are considered to be a promising CO2 adsorbent because of their adjustable pore size structure, good thermal stability and large specific surface area.
[0005] The carbon content of straw is generally above 50%, and it is a typical precursor of porous biochar materials. The carbon material skeleton contains multiple functional groups such as hydroxyl, carboxyl, and ether. Specific functional groups can be introduced through "assembly reactions" such as chemical doping and surface modification, thereby achieving efficient and selective adsorption of pollutants. In addition, by adjusting the pore structure of the carbon material, its physical adsorption sites can be increased, the mass transfer performance of the gas can be improved, and the gas adsorption capacity can be further improved. It has the advantages of strong adsorption capacity and low energy consumption.
[0006] CO2 is a non-polar molecule, and the surface of carbon materials is also non-polar. Under normal temperature and pressure conditions, the adsorption capacity of carbon materials for CO2 gas is very low. Therefore, it is necessary to precisely control the chemical functional groups and pore structure on the surface of carbon materials. (1) In the preparation process of conventional carbon materials, the surface chemical functional groups are mainly modified by wet chemical methods to increase the content of their functional groups in a targeted manner. However, porous carbon is a hydrophobic material, which leads to a very limited loading of chemical functional groups in a system with aqueous solution as solvent. In the modification process, the carrier and the modifier are even stratified, eventually forming an invalid load. Due to the asymmetry of their structure, ionic liquids cannot regularly stack into crystals, resulting in them being in liquid form at room temperature or near room temperature, thereby greatly enhancing the solubility of porous carbon materials. Compared with aqueous solution systems, ionic liquids have unique advantages such as good atom economy, good biocompatibility, and low toxicity, which are conducive to the synthesis of carbon material adsorbents with high chemical functional group content. (2) Ionic liquids are mostly macromolecules. When in contact with carbon materials, they tend to block the pores of carbon materials, thereby reducing the mass transfer efficiency of carbon dioxide in the carbon material matrix. Physical and chemical activation of carbon materials can expand the pore structure of carbon materials and develop most of the micropores into mesopores, which is conducive to the subsequent interaction between carbon carriers and ionic liquids and promotes the loading of active components. At the same time, a large number of new oxygen-containing groups will form on the surface of biochar, which synergistically promotes the interaction between the carrier and the active components.
[0007] The incorporation of strong electronegative groups can effectively adjust the electronic properties of carbon materials, change the acid-base properties of the carrier, improve the acid-base tolerance of the material, electronic interaction, and accelerate electron transfer. By introducing active functional groups (such as amino, thiol, carbonyl) on the surface of the adsorption material and increasing its surface alkalinity, the adsorption capacity of CO2 and NO acidic gases on the carbon material can be greatly increased. For example, the O atom in the CO2 molecule has a strong electron-removing property, which makes the carbon atom electrophilic. When the C atom is close to the electronegative and rich lone pair electrons (amino, thiol), it will have a strong acid-base interaction with it, thereby enhancing the capture of CO2 and NO gases. The cost of preparing functional carbon materials will also be reduced, and the material will have great economic and environmental benefits. Summary of the invention
[0008] The purpose of the present invention is to overcome the shortcomings of the prior art, and to provide a preparation system for ion liquid cascade metal inorganic salt, white carbon black and chitosan activation treatment of straw, and a method for synthesizing mesoporous biochar adsorption material. The integrated pretreatment method of carbonization and activation can not only increase the alkaline O functional groups on the surface of the modified carbon material, but also improve the number and proportion of mesoporous structures of the carbon carrier, significantly increase the number of pores for the ionic liquid to enter the matrix, and further promote the interaction between the ionic liquid and the carbon skeleton, realize the efficient loading of S, N, O active groups, and significantly increase its chemical adsorption capacity for carbon dioxide and nitric oxide gases.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] A method for preparing a modified mesoporous biochar adsorbent comprises the following steps:
[0011] ⑴ Crushing, washing and drying the straw raw materials to obtain straw powder;
[0012] (2) Mixing the obtained straw powder with chitosan, metal inorganic salt and white carbon black for ball milling pretreatment;
[0013] (3) carbonizing and activating the solid mixture in step (2) at high temperature in a mixed gas atmosphere of nitrogen and water vapor;
[0014] (4) washing the product in step (3) with a detergent, washing with ultrapure water until the pH is neutral, and vacuum drying to obtain mesoporous straw-based biochar;
[0015] (5) Mix the mesoporous straw-based biochar with the pyrrolidine ionic liquid and the organic solvent in a specific ratio, place them in an ultrasonic cleaner for mixing for 0.5-3 hours, and dope nitrogen and sulfur atoms;
[0016] ⑹ Transfer the mixture described in ⑸ to a rotary evaporator and dry it to obtain the ionic liquid modified mesoporous biochar material.
[0017] Moreover, the metal inorganic salt is one or more of zirconium oxynitrate, calcium chloride and tin chloride; the mass ratio of the added amount of the metal inorganic salt to the straw is 1:3-6.
[0018] Moreover, the white carbon black is nano-scale white carbon black with a particle size range of 20nm-50nm, the weight ratio of the white carbon black to the straw is 1:4-1:20, and the mass ratio of the chitosan addition amount to the straw is 1:0.5-3.
[0019] Moreover, the ball milling speed is 300-600 rpm, the mechanical ball milling time is 0.5-12 h, and the operation is stopped for 0.5 h after each 0.5 h of operation.
[0020] Moreover, the carbonization activation integrated reaction temperature of the nitrogen and water vapor mixed atmosphere is 650° C.-950° C., the reaction time is 1-4 hours, and the heating rate is 1-5° C. / min; the volume fraction of the water vapor is 0.04%-0.1%.
[0021] Moreover, the detergent is 10-20% hydrofluoric acid, the washing times are 1-2 times; the vacuum drying temperature is 60-80° C., and the drying time is 12-24 hours.
[0022] Moreover, the pyrrolidine ionic liquid is a mixture of one or more of 1-butyl-1-methylpyrrolidine trifluoromethanesulfonate, 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, and 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide; the ratio of the added amount of the pyrrolidine ionic liquid to the mesoporous straw-based biochar is 1:1-1:5.
[0023] Moreover, the organic solvent is a mixture of one or more of n-propanol and isopropanol, and the added amount of the organic solvent is 5-10 mL / g.
[0024] Moreover, the straw raw material is durian shell straw.
[0025] The ionic liquid modified mesoporous biochar adsorbent prepared by the above method is used as an adsorbent for gaseous carbon dioxide and / or nitric oxide acidic gases.
[0026] The advantages and positive effects of the present invention are as follows:
[0027] In the integrated high-temperature carbonization and activation process of the present invention, white carbon black can be embedded in the mesopores and macropores in the cellulose and hemicellulose structures of the biochar through the cross-linking effect of chitosan. Subsequently, when the white carbon black is removed by washing with hydrofluoric acid, mesoporous vacancies are formed in the pore structure of the biochar, thereby greatly increasing the amount of ionic liquid that can enter the biochar matrix and significantly promoting the loading of active electronegative groups (S, N, O, etc.).
[0028] The present invention removes white carbon black through hydrofluoric acid washing to obtain high-mesopore ratio straw-based biochar, which is beneficial for subsequent active components to enter the biochar pores without blocking the pores. At the same time, the adsorbent after the active components are loaded on the high-mesopore ratio carrier also maintains a certain specific surface area for the mass transfer of CO2 and NO in the flue gas within the pore structure of the material, thereby significantly enhancing the adsorption of CO2 and NO gases on the non-polar carbon material.
[0029] The carbonization activation integrated reaction temperature of the present invention in the nitrogen and water vapor mixed atmosphere is 650℃-950℃, and high-temperature carbonization activation obtains highly stable porous carbon, which overcomes the problem of poor stability of carbon materials prepared by hydrothermal method. The metal inorganic salt under high temperature conditions can expand the pore structure of the carrier through physical action, and generate new alkaline oxygen-containing active sites through chemical action, thereby significantly increasing the active adsorption sites of the biochar material.
[0030] The modification process of the present invention is to pretreat the mesoporous straw-based biochar with ionic liquid and couple it with rotary evaporation and mixing. The ionic liquid is used as a solvent to increase the solubility of the mesoporous straw-based biochar in the modifier. In addition, the ionic liquid can also be used as an activator to ultimately promote the formation of modified mesoporous straw-based biochar.
[0031] In the preparation process of the present invention, chitosan is added, and the chitosan is coupled with ball milling mixing and high-temperature activation, which can not only embed white carbon black into the mesopores and macropores of the biochar cellulose and hemicellulose structures, but also serve as a nitrogen source in the subsequent rotary evaporation modification process to achieve in-situ incorporation of nitrogen atoms.
[0032] The present invention uses n-propanol and isopropanol as pyrrolidine ionic liquid loading solvents, and can further increase the content of oxygen-containing functional groups (COOH, CHO) on the surface of the prepared material through ultrasonic treatment coupled with a rotary evaporation modification process, while synergistically introducing other electronegative functional groups (S, N, etc.) to promote the adsorption of carbon dioxide and nitric oxide gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 FTIR spectrum of the material in Application Example 1 of the present invention;
[0034] Figure 2 This is a scanning electron microscope image of the material in Example 1 of the present invention;
[0035] Figure 3 This is a scanning electron microscope image of the material in Example 2 of the present invention;
[0036] Figure 4 This is a scanning electron microscope image of the material in Example 3 of the present invention. DETAILED DESCRIPTION
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0038] The present invention also provides a modified mesoporous biochar adsorbent obtained by the preparation method described in the above scheme, including a mesoporous biochar adsorbent and a modified mesoporous biochar adsorbent. The present invention also provides the use of the modifier-modified mesoporous biochar adsorbent described in the above scheme as an adsorption material. The modifier-modified mesoporous biochar adsorbent of the present invention is used as an adsorption material to efficiently remove gaseous pollutants in industrial flue gas, and is particularly suitable for carbon dioxide and nitric oxide gases.
[0039] In the present invention, the ionic liquid includes pyrrolidine ionic liquid, not limited to one of them. The present invention washes the straw raw material and dries it, mixes it with mechanical ball milling to obtain powder. In the present invention, the straw is preferably durian straw, and also includes rice straw, corn straw, wheat straw, etc., but the mesoporous proportion of durian straw is the best, not limited to one of them. The present invention uses solid waste straw as raw material, realizes the recycling and reuse of solid waste, and through high-temperature desorption, the material can be recycled for many times, which meets the requirements of sustainable development, and also avoids environmental problems caused by combustion.
[0040] The present invention provides an ionic liquid modified mesoporous biochar adsorbent and a preparation method thereof, comprising the following steps:
[0041] ⑴ Crushing, washing and drying the straw raw materials to obtain straw powder;
[0042] (2) The obtained straw powder is mixed with chitosan, metal inorganic salt and white carbon black for ball milling pretreatment; the metal inorganic salt is one or more of zirconium nitrate, calcium chloride and tin chloride; the mass ratio of the metal inorganic salt to the straw is 1:3-6. The white carbon black is nano-scale white carbon black with a particle size range of 20nm-50nm, the weight ratio of the white carbon black to the straw is 1:4-1:20, and the mass ratio of the chitosan addition to the straw is 1:0.5-3. The ball milling speed is 300-600rmp, the mechanical ball milling time is 0.5-12h, and the operation is stopped for 0.5h after each 0.5h of operation.
[0043] ⑶ Carbonize and activate the solid mixture described in step ⑵ at high temperature in a mixed gas atmosphere of nitrogen and water vapor; the integrated reaction temperature of carbonization and activation in the mixed atmosphere of nitrogen and water vapor is 650°C-950°C, the reaction time is 1-4h, and the heating rate is 1-5°C / min; the volume fraction of the water vapor is 0.04%-0.1%.
[0044] (4) After washing the product in step (3) with a detergent, wash it with ultrapure water until the pH is neutral, and vacuum dry it to obtain mesoporous straw-based biochar; the detergent is 10-20% hydrofluoric acid, and the number of washings is 1-2 times; the vacuum drying temperature is 60-80°C, and the drying time is 12-24h.
[0045] (5) Mix the mesoporous straw-based biochar with pyrrolidine ionic liquid and organic solvent in a specific ratio, place in an ultrasonic cleaner for mixing for 0.5-3h, and dope nitrogen and sulfur atoms; the pyrrolidine ionic liquid is a mixture of one or more of 1-butyl-1-methylpyrrolidine trifluoromethanesulfonate, 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, and 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide; the ratio of the amount of the pyrrolidine ionic liquid added to the mesoporous straw-based biochar is 1:1-1:5. The organic solvent is a mixture of one or more of n-propanol or isopropanol, and the amount of the organic solvent added is 5-10mL / g.
[0046] ⑹ Transfer the mixture described in ⑸ to a rotary evaporator and dry it to obtain the ionic liquid modified mesoporous biochar material.
[0047] Application of modified mesoporous biochar adsorbent as gaseous carbon dioxide and / or nitric oxide gas adsorption material.
[0048] The purpose of the present invention is to produce mesoporous biochar with a mesoporous specific surface area of 478.7 m 2 / g, white carbon black promotes the formation of mesopores, and after hydrofluoric acid cleaning, the solid becomes hollow, chitosan increases the adhesion of white carbon black and cellulose and hemicellulose and dopes N functional groups, and metal salts can increase mesopores and provide oxygen-containing functional groups. The present invention expands the pore structure of carbon materials and realizes the directional synthesis of high-mesoporous ratio biochar by mixing mechanical ball milling pretreatment cascade high-temperature carbonization activation integrated treatment mode, which is beneficial to the subsequent interaction between carbon carriers and ionic liquids, and promotes the loading of active components and the mass transfer of CO2 and NO gases in flue gas.
[0049] After the biochar doped with metal salts is heat treated, not only the pore structure of the carbon material is developed, but also the crystal structure of the metal salt is transformed into metal oxides. 2- It can form active adsorption sites and synergistically promote the interaction between the carrier and the active components. The biochar matrix is easy to break, and white carbon black is hard and dense. It can be embedded in the mesopores and macropores of the biochar cellulose and hemicellulose structure. After high-temperature carbonization and activation, a large number of new mesopores are formed, which play a role in supporting the internal pores.
[0050] The present invention uses pyrrolidine ionic liquid coupled with ultrasonic treatment to uniformly mix the carrier and the modifier, and simultaneously the microprojectiles generated based on the cavitation effect impact the surface of the carbon material to promote the formation of micropores. In addition, the ultrasonic treatment can also peel off the graphite layer of the biochar, so that more active sites are exposed, which greatly increases the load of the active group and improves the economy of the preparation method. There is no molecular configuration substance in the ionic liquid, which greatly reduces the solvation process, and then significantly increases the solubility of the non-polar non-water-soluble carbon material, thereby increasing the contact area between the modifying agent and the non-polar mesoporous biochar carrier, and significantly promotes the load of electronegative groups (S, N, O, etc.).
[0051] The present invention reduces the particle size of straw by pretreatment with mixed mechanical ball milling, i.e., metal inorganic salt, white carbon black and chitosan coupled mechanical ball milling, which can promote the decomposition of biomass straw pyrolysis carbonization process, and finally promote the formation of highly graphitized straw-based biochar. In addition, white carbon black significantly improves the mesoporous ratio and specific surface area of biochar adsorbent through high-temperature carbonization and activation integrated treatment; and ultrasonic synergistic high-temperature rotary evaporation treatment can further increase the chemical adsorption sites of mesoporous biochar; the addition of ionic liquid can be used as a solvent to increase the solubility of straw, and can also be used as a modifier to in-situ modify the electronegative groups such as nitrogen and sulfur on the surface of biochar, and promote the formation of highly active modified biochar.
[0052] The modified mesoporous straw-based biochar adsorbent material of the present invention removes carbon dioxide and nitric oxide by adsorption. The used adsorbent can be repeatedly recycled by high-temperature activation, and has great economic and environmental value. The results of the embodiment show that the modified mesoporous straw-based biochar material prepared by the present invention as an adsorbent has a static saturated adsorption capacity of carbon dioxide at room temperature and pressure and a dynamic saturated adsorption capacity of nitric oxide gas of up to 4.0 mmol / g and 218.7 mg / g.
[0053] In the process of mechanical ball milling pretreatment, the addition of chitosan, metal inorganic salts and white carbon black can reduce the polymerization degree of straw, increase the proportion of alkaline oxygen-containing functional groups and mesoporous structures of straw, and is conducive to increasing the contact area between the modifier and the carrier in the next impregnation modification process, thereby promoting the loading of active functional groups and promoting the mass transfer of carbon dioxide and nitric oxide in flue gas. Pre-addition of metal salts, white carbon black and chitosan in mechanical ball milling pretreatment can cooperate with ionic liquid solvents to promote the formation of carbon carrier adsorption materials.
[0054] The present invention verifies, according to the examples, that metal inorganic salts can promote the carbon dioxide or carbon monoxide released during the high-temperature carbonization activation process to expand the microporous structure of the carbon carrier, and further promote the polymerization or aromatization of the biochar material by oxidizing the carbon framework, thereby significantly increasing the adsorbent porosity and the surface alkaline oxygen functional group content. The high-temperature carbonization activation integrated process can promote white carbon black to enter the cellulose and hemicellulose structure of the straw carbon, and ultimately promote the formation of a high-mesoporous ratio biochar carrier.
[0055] Example 1
[0056] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0057] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0058] (2) Place 6 g of durian shell powder, 3 g of chitosan powder, 1.5 g of zirconium oxynitrate powder and 1.2 g of white carbon black in a ball mill and mill them at 400 rpm for 4 h to obtain a modified mixture.
[0059] ⑶ The modified mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min in a mixed gas atmosphere of nitrogen (200 mL / min) and water vapor (0.1 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0060] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0061] (5) Mix the mesoporous straw-based biochar with 3 g of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and 50 mL of isopropanol solvent, place in an ultrasonic cleaner and mix for 1.5 h to dope nitrogen and sulfur atoms;
[0062] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0063] Example 2
[0064] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0065] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0066] (2) Place 6 g of durian shell powder, 1.5 g of zirconium oxynitrate powder and 1.2 g of white carbon black in a ball mill and mill them at 400 rpm for 4 h to obtain a modified mixture.
[0067] ⑶ The solid mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min in a mixed gas atmosphere of nitrogen (200 mL / min) and water vapor (0.1 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0068] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0069] (5) Mix the mesoporous straw-based biochar with 3 g of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and 50 mL of isopropanol solvent, place in an ultrasonic cleaner and mix for 1.5 h to dope nitrogen and sulfur atoms;
[0070] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0071] Example 3
[0072] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0073] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0074] (2) Place 6 g of durian shell powder, 3 g of chitosan powder and 1.2 g of white carbon black in a ball mill and mill them at 400 rpm for 4 h to obtain a modified mixture.
[0075] ⑶ The solid mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min in a mixed gas atmosphere of nitrogen (200 mL / min) and water vapor (0.1 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0076] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0077] (5) Mix the mesoporous straw-based biochar with 3 g of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and 50 mL of isopropanol solvent, place in an ultrasonic cleaner and mix for 1.5 h to dope nitrogen and sulfur atoms;
[0078] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0079] Example 4
[0080] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0081] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0082] (2) Place 6 g of durian shell powder, 3 g of chitosan powder and 1.5 g of zirconium oxynitrate powder in a ball mill and mill them at 400 rpm for 4 h to obtain a modified mixture.
[0083] ⑶ The solid mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min in a mixed gas atmosphere of nitrogen (200 mL / min) and water vapor (0.1 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0084] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0085] (5) Mix the mesoporous straw-based biochar with 3 g of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and 50 mL of isopropanol solvent, place in an ultrasonic cleaner for mixing for 1.5 h, and dope nitrogen and sulfur atoms;
[0086] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0087] Example 5
[0088] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0089] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0090] (2) Place 6 g of durian shell powder and 1.5 g of calcium chloride powder in a ball mill and mill them at 400 rpm for 4 h to obtain a modified mixture.
[0091] ⑶ The solid mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min in a mixed gas atmosphere of nitrogen (200 mL / min) and water vapor (0.1 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0092] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0093] (5) Mix the mesoporous straw-based biochar with 3 g of 1-butyl-1-methylpyrrolidine trifluoromethanesulfonate and 50 mL of isopropanol solvent, place in an ultrasonic cleaner and mix for 1.5 h to dope nitrogen and sulfur atoms;
[0094] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0095] Example 6
[0096] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0097] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0098] (2) Place 6 g of durian shell powder, 3 g of chitosan powder, 1.5 g of zirconium oxynitrate powder and 1.2 g of white carbon black in a ball mill and mill them at 400 rpm for 4 h to obtain a modified mixture.
[0099] ⑶ The solid mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min under a nitrogen atmosphere (200 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0100] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0101] (5) Mix the mesoporous straw-based biochar with 3 g of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and 50 mL of isopropanol solvent, place in an ultrasonic cleaner and mix for 1.5 h to dope nitrogen and sulfur atoms;
[0102] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0103] Example 7
[0104] A method for preparing a modified mesoporous biochar adsorbent, comprising the following steps:
[0105] ⑴ The durian shell powder raw material was crushed, 5% dilute sulfuric acid was added, and stirred for 20 minutes to remove impurities and ash, and then dried in a vacuum drying oven at 60°C for 24 hours to obtain straw powder. The crushed straw powder was above 40 meshes;
[0106] (2) Place 6 g of durian shell powder in a ball mill and ball mill it at 400 rpm for 4 h to obtain a modified mixture.
[0107] ⑶ The solid mixture described in step ⑵ was heated to 850° C. at a rate of 2.5° C. / min in a mixed gas atmosphere of nitrogen (200 mL / min) and water vapor (0.1 mL / min), and carbonized and activated at 850° C. for 2 h to obtain modified biochar;
[0108] (4) Add 1.2 L of 10% hydrofluoric acid to the product in step (3) and stir for 6 h, then wash with ultrapure water until the pH of the supernatant is 7, filter and dry in a vacuum drying oven at 60° C. for 12 h to obtain mesoporous straw-based biochar;
[0109] (5) Mix the mesoporous straw-based biochar with 3 g of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and 50 mL of isopropanol solvent, place in an ultrasonic cleaner for mixing for 1.5 h, and dope nitrogen and sulfur atoms;
[0110] (6) Dry the mixture described in (5) on a rotary evaporator at 80°C for 8 hours to obtain a modified mesoporous biochar material. After obtaining the material, perform an adsorption experiment.
[0111] Adsorption performance test:
[0112] In the present invention, the modified mesoporous biochar material and the carbon dioxide waste gas are preferably mixed by standing for a long time, the temperature of the adsorption treatment is preferably room temperature, the room temperature is preferably 25°C, the simulated flue gas is composed of 100% carbon dioxide gas, the carbon dioxide adsorbent (modified mesoporous biochar material) is loaded in an amount of 200 mg, and the pressure of the carbon dioxide adsorption treatment is 1 atmosphere. The modified mesoporous biochar material and the nitric oxide waste gas are preferably mixed by dynamic adsorption, the temperature of the adsorption treatment is preferably room temperature, the room temperature is preferably 25°C. The pressure of the nitric oxide adsorption treatment is 1 atmosphere, and the air velocity is 9600h -1 The total flow rate of simulated flue gas is 500 mL / min, the volume concentration of nitric oxide gas in the simulated flue gas is 500 ppm, and the carrier gas is argon.
[0113] Table 1 Performance evaluation results of different modified mesoporous biochar adsorbents
[0114]
Claims
1. A method for preparing a modified mesoporous biochar adsorbent, characterized in that: The following steps are involved: ⑴ Crushing, washing and drying the straw raw materials to obtain straw powder; (2) Mixing the obtained straw powder with chitosan, metal inorganic salt and white carbon black for ball milling pretreatment; (3) carbonizing and activating the solid mixture of step (2) at high temperature in a mixed atmosphere of nitrogen and water vapor; (4) washing the product of step (3) with a detergent, washing with ultrapure water until the pH is neutral, and vacuum drying to obtain mesoporous straw-based biochar; (5) Mix the mesoporous straw-based biochar with pyrrolidine ionic liquid and organic solvent in a specific ratio, place in an ultrasonic cleaner for mixing for 0.5-3 h, and dope nitrogen and sulfur atoms; (6) Transfer the mixture of (5) to a rotary evaporator and dry to obtain the ionic liquid modified mesoporous biochar material; The metal inorganic salt is one or more of zirconium oxynitrate, calcium chloride, and tin chloride; the mass ratio of the metal inorganic salt added to the straw is 1:3-6; The white carbon black is nano-scale white carbon black with a particle size range of 20nm-50nm, the weight ratio of the white carbon black to the straw is 1:4-1:20, and the mass ratio of the chitosan addition amount to the straw is 1:0.5-3; The carbonization activation integrated reaction temperature of the nitrogen and water vapor mixed atmosphere is 650°C-950°C, the reaction time is 1-4 h, and the heating rate is 1-5°C / min; the volume fraction of the water vapor is 0.04%-0.1%; The detergent is 10-20% hydrofluoric acid, and the number of washings is 1-2 times; the vacuum drying temperature is 60-80°C, and the drying time is 12-24 h; The pyrrolidine ionic liquid is a mixture of one or more of 1-butyl-1-methylpyrrolidine trifluoromethanesulfonate, 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, and 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide; the ratio of the pyrrolidine ionic liquid to the mesoporous straw-based biochar is 1:1-1:5; The organic solvent is a mixture of one or more of n-propanol and isopropanol, and the amount of the organic solvent added is 5-10 mL / g.
2. The method for preparing the modified mesoporous biochar adsorbent according to claim 1, characterized in that: The ball milling speed is 300-600 rpm, the mechanical ball milling time is 0.5-12 h, and the operation is stopped for 0.5 h after each 0.5 h of operation.
3. The method for preparing the modified mesoporous biochar adsorbent according to claim 1, characterized in that: The straw raw material is durian shell straw.
4. Use of the modified mesoporous biochar adsorbent prepared by the preparation method of any one of claims 1 to 3 as a gaseous carbon dioxide and / or nitric oxide gas adsorption material.
